2017
DOI: 10.1080/03007995.2017.1400962
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of using an extensively hydrolyzed casein formula containing Lactobacillus rhamnosus GG in managing infants with cow’s milk allergy in the US

Abstract: Initial management of newly-diagnosed cow's milk allergic infants with eHCF + LGG was found to afford a cost-effective strategy to both third-party insurers and parents when compared to an eHCF alone or an AAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…9,18 Previous economic analyses were conducted assessing the costeffectiveness of hypoallergenic formulas, but these were based on efficacy evidence collected over a maximum of 18 months. [20][21][22][23][24] A recent publication reported on the incidence of allergic manifestation and cow's milk tolerance over three years, in children treated with different formulas. 25 To inform clinical practice and health system efficiency, we compared the cost-effectiveness of amino acid-based formula (AFF), extensively hydrolysed casein formula containing Lactobacillus rhamnosus Gorbach Goldin (EHCF+LGG), extensively hydrolysed whey formula (EHWF), and soy formula (SF), in managing CMPA in children.…”
mentioning
confidence: 99%
“…9,18 Previous economic analyses were conducted assessing the costeffectiveness of hypoallergenic formulas, but these were based on efficacy evidence collected over a maximum of 18 months. [20][21][22][23][24] A recent publication reported on the incidence of allergic manifestation and cow's milk tolerance over three years, in children treated with different formulas. 25 To inform clinical practice and health system efficiency, we compared the cost-effectiveness of amino acid-based formula (AFF), extensively hydrolysed casein formula containing Lactobacillus rhamnosus Gorbach Goldin (EHCF+LGG), extensively hydrolysed whey formula (EHWF), and soy formula (SF), in managing CMPA in children.…”
mentioning
confidence: 99%
“…However, the economic analysis also showed that initial management with eHCF plus LGG affords a cost-effective dietetic strategy over a period of 3 years across all measures of effectiveness. Additionally, we have previously reported that initial management of both IgE-mediated and non-IgE-mediated CMPA with eHCF plus LGG affords a cost-effective dietetic strategy when compared to both an eHCF alone and amino acid formulae over a period of 18 months in different countries [6][7][8][9][10] . Consequently, our studies would suggest that the probability of eHCF plus LGG being a cost-effective formula for the initial management of CMPA is sustained from 18 months over a period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies comparing different formulae found that feeding cow's milk allergic children with an extensively hydrolyzed casein formula (eHCF) supplemented with the probiotic Lactobacillus rhamnosus GG (LGG) (Nutramigen à LGG V R ; eHCF plus LGG) resulted in higher acquisition of tolerance to cow's milk protein compared with those fed an eHCF without LGG and other formulae 4,5 . Additionally, feeding eHCF plus LGG first line to both immunoglobulin E (IgE)-mediated and non-IgE-mediated cow's milk allergic infants, compared to feeding with an eHCF alone or an amino acid formula, was found to be cost-effective in Italy 6 , Spain 7 , Poland 8 and the US 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…1), covering 3 types of food allergy and published between 2009 and 2019. Eight papers investigated PA, [24][25][26][27][28][29][30][31] 8 investigated CMA, [32][33][34][35][36][37][38][39] and 1 focused on EA. 40…”
Section: Resultsmentioning
confidence: 99%